Politics of human rights :The quest for dignity - Carey, Sabine C. (Cambridge University Press, 2010)
"Human rights is an important issue in contemporary politics, and the last few decades have seen a remarkable increase in research and teaching on the subject. This book introduces students to the study of human rights and aims to build on their interest while simultaneously offering an alternative vision of the subject. Many texts focus on the theoretical and legal issues surrounding human rights. This book adopts a substantially different approach which uses empirical data derived from research on human rights by political scientists to illustrate the occurrence of different types of human rights violations across the world. The authors devote attention to rights as responsibilities as well as to responsibilities, which do not stop at one country's political borders. They also explore how to deal with repression and the aftermath of human rights violations, making students aware of the prospects for and realities of progress"--Provided by publisher.